2015
DOI: 10.1515/jtes-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Stress Levels of Early Childhood, Primary and Secondary Pre-service Teachers during Teaching Practicum

Abstract: This study investigated stress levels of pre-service teachers (PSTs) across three categories of teaching context: early childhood, primary and secondary. This paper focused on exploring the stressors in the completion of tasks in teaching practicum in the three categories of teaching context and an awareness of and access to support systems. The Perceived Stress Scale (PSS) and an online questionnaire were used to measure the nature and level of stress. Significant results were found in relation to the school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…That is, they are required to undertake teaching practicum on top of a theoretical study load which worsens the already stressful environment. It has been frequently reported that the teaching practicum was rated as the most stressful study task for early childhood teacher candidates, which needs to be seen in the context of their stress levels strongly influencing their decision to stay in the teaching profession [5]. Practicum-related stressors experienced by early childhood teacher candidates include the gap between theoretical knowledge and field experience in the ECE profession, which includes the discrepancy between what is taught in the classroom and how nurture and support are actually provided in practice, the associated psychological burden, and the lack of preparation as a prospective early childhood teacher.…”
Section: Introductionmentioning
confidence: 99%
“…That is, they are required to undertake teaching practicum on top of a theoretical study load which worsens the already stressful environment. It has been frequently reported that the teaching practicum was rated as the most stressful study task for early childhood teacher candidates, which needs to be seen in the context of their stress levels strongly influencing their decision to stay in the teaching profession [5]. Practicum-related stressors experienced by early childhood teacher candidates include the gap between theoretical knowledge and field experience in the ECE profession, which includes the discrepancy between what is taught in the classroom and how nurture and support are actually provided in practice, the associated psychological burden, and the lack of preparation as a prospective early childhood teacher.…”
Section: Introductionmentioning
confidence: 99%
“…The research review by Hoffman et al (2015) suggests that intensive learning assistance is essential for handling professional challenges during an internship. The findings of Ekşi and Yakışık (2016) and Geng, Midford, and Buckworth (2015) show that support during internships can reduce student teachers' anxieties and stress. Richter et al (2013) demonstrated positive effects from constructive support through mentoring, even for career beginners.…”
Section: Student Teachers Experiencing Stress In Internshipsmentioning
confidence: 95%
“…Moreover, new transdisciplinary turn has been noticed not only in philosophical background of the papers (see the next section of the paper), but also in six papers whose authors represented, using the terminology of transdisciplinary paradigm, different types of stakeholders (Mauser et al, 2013). Thus, in paper by Geng, Midford, and Buckworth (2015) the stress level of pre-service teachers during teaching practicum was explored in collaboration between the Charles Darwin University academics and representative from the Menzies School of Health. The author of the paper on the teacher ecological self Rea Raus (2016) represents both the academic institution and NGO (University of Tampere and Statera Research and Practice Center for Sustainability), while Bikse and her colleagues from Latvia (2016), who analysed the transformation of universities toward entrepreneurial universities, are academics from two universities and BA School of Business and Finance.…”
Section: Main Bibliometric Indicators (Jtes 2015ñ2018)mentioning
confidence: 99%